Modeling and leveling of categories affecting the geographical landscape form of the world - Leyla Meshkani; Jamile tavakolinia; mohamad taghi Razavian (تحقیقات کاربردی علوم جغرافیایی)
Landscapes cannot be explained only by obscure geographical frequencies that can be described by objective methods, but they are real subjective observations and experiences that can be inferred by artistic and aesthetic perception, analysis and comparison. Thus, recognizing the elements of the emergence, formation and development of any perspective can be considered as a mirror of the whole picture of human knowledge, culture and perceptions in geography. It is based on such an understanding that the present study attempts to combine qualitative content analysis techniques and soft operations based on interpretive philosophy with a qualitative approach to the question of why each geographical (urban) landscape emerges. Thus, by analyzing the content of printed resources in this field, 14 categories were extracted, and the experts answered the questions related to the role of each category by using the evaluation questionnaire. Finally, after collecting the questionnaires from 10 geography experts, with the help of Fuzzy DEMATEL technique, the existing relationships between categories were analyzed and finally, due to the defect and inability of this technique in leveling, the effective levels between categories were determined by ISM technique. In the meantime, the results indicated that the worldview category, which in the general sense includes religious and ideological concept, is considered as an independent variable of the geographical landscape system. At other levels, there is civic awareness, philosophical thought, and political thought, which serve as the basis for the geographical landscape. In this context, the perspective variables of context, governance, cultural dimensions, and social context are defined as the moderating variables of the geographical landscape system. From the set interaction of variables mentioned, such as the organization of living space, reading of living space, public and private agreement and social resilience are obtained.